Tailored bainitic-martensitic microstructures by means of inductive surface hardening for AISI4140. (October 2020) - Mühl, F.; Jarms, J.; Kaiser, D.; Dietrich, S.; Schulze, V.
Abstract: Inductive surface hardening processes are widely used in the manufacturing of automotive parts. They combine short process times with high economic and energy efficiency. Because of their high surface hardness, induction hardened steel parts feature beneficial wear resistance and also good fatigue properties due to the induced compressive residual stresses in the surface. Considering the positive effects on the mechanical properties by creating a bainitic-martensitic microstructure, outlined by severel authors, this study includes the implementation of a temperature controlled inductive surface hardening process on a conventional hardening machine. Therefore an innovative inductor design, which allows a controlled sample cooling is presented. Supported by dilatometric studies as well as different heat treatment strategies, limitations are identified to gain a profund process understanding. Hereby an accelerated bainite formation after short time austenitization is detected. By using different heat treatment strategies, the fraction of the bainitic phase can be adjusted in the surface of the part made of AISI 4140. The results of this innovative heat treatment method are compared to short time inductive hardening and tempering processes regarding microstructure, hardness and residual stresses. The generated surface layer states, including mixed microstructures, show promising properties resulting in a possible enhancement of the fatigue strength of induction hardened parts. Graphical abstract: Unlabelled Image Highlights: Innovative concept for the inductor that enables a cooling with compressed air during induction hardening. Investigations of bainitic phase transformation after short time austenitization. Development different heat treatment strategies creating bainitic-martensitic microstructures by means of induction hardening. Improvement of the surface layer state of induction hardened parts.